Clinical analysis of secondary hemophagocytic syndrome in children in Gansu province - Zhou, Yongkang; Yang, Junqiang; Tao, Zhongbin (Frontiers in Pediatrics, 2025)
ObjectiveThis study aims to explore and analyze the various causes, clinical features, and prognostic differences of secondary hemophagocytic syndrome (SHS) in children in Gansu Province, China.MethodThis study used a retrospective analysis method, selected 43 children with HLH who were treated in the PICU at the First Hospital of Lanzhou University from January 2019 to January 2025. Based on their primary diseases, the subjects were categorized into groups for VL, EB virus infection, and other infections. The clinical manifestations, laboratory results and clinical outcomes of each group were comprehensively analyzed.ResultsThe main cause of HLH was infection (35/43 cases), with EB virus infection (15/35 cases) and leishmania (13/35 cases) being the most common. In the leishmania and EB virus infection group, the average of alanine aminotransferase (ALT) levels were 81 U/L and 87 U/L respectively, were higher than other infection group (P < 0.05). The average of procalcitonin (PCT) levels were 2.88 ng/mL, 4.37 ng/mL respectively in the Leishmania group and other infection group, were higher than EBV infection group(0.43 ng/mL). The average of D-dimer (D-D) levels were statistically significant differences among Leishmania group(2.31 mg/dL), EBV infection group(2.12 mg/dL) and the other infection group (3.34 ng/mL). The leishmania group had a cure rate of 100% (13/13), while the EB virus infection group had a cure rate of 26.67% (4/15).ConclusionLeishmania and EB virus infection are common causes of HLH in Gansu Province. Compared to HLH caused by other factors such as EB virus infection or autoimmune diseases, the prognosis of HLH in children with leishmania infection is relatively better.